Building material of phase-change difunctional microcapsule prepared based on needle-based microfluidic control and application of building material
By preparing phase-change dual-function microcapsules based on needle-based microfluidic control technology, the leakage, low conductivity and corrosion problems of existing phase-change materials in building materials are solved, and the effective application of dual-function microcapsules in building materials is achieved, with good thermal regulation performance and photocatalytic capabilities.
Patent Information
- Application Number
- CN202411037423.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-03-11
AI Technical Summary
The application of existing phase change materials in building materials has problems of leakage, low conductivity and corrosion, and traditional preparation methods are difficult to achieve monodispersed microcapsules with uniform size and uniform polymer shell thickness.
Phase-change dual-function microcapsules were prepared by using technology based on needle-based microfluidic control. Microcapsules with core-shell structures were formed by n-hexadecane, HDDA and TiO2 as internal, medium and external phase fluids by ultraviolet photopolymerization, and added to gypsum.
It realizes the effective application of dual-function microcapsules in building materials, has good thermal regulation performance and photocatalytic capabilities, and improves the thermal inertia and temperature regulation stability of building materials.
Smart Images

Figure CN119591370A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and in particular to a building material of phase-change dual-function microcapsules prepared based on needle-based microfluidics and its application. Background Art
[0002] Thermal energy storage (TES) based on sunlight offers a promising avenue to address environmental challenges and reduce dependence on fossil fuels. At the heart of TES systems are phase change materials (PCMs), which can absorb, retain, and release large amounts of heat at a constant temperature. PCMs have been used in a variety of applications, including building materials, medicine, food packaging, and electronic cooling. However, they have several limitations, such as leakage, low conductivity, and corrosiveness. To overcome these challenges, various confinement techniques, such as microencapsulation, have been developed. Microencapsulation involves coating tiny PCM droplets with film-forming materials to prevent leakage and control volume during phase change. This technique has proven to be effective in addressing the inherent problems associated with PCMs, making them more practical for a variety of applications. However, with the widespread use of microencapsulation technology, higher standards and efficiency requirements have been placed on the monodispersity and uniformity of microcapsules, which cannot be met by traditional preparation methods. Polymer shell-based microcapsules are usually prepared by various chemical techniques, including interfacial polymerization, in situ polymerization, microemulsion polymerization, and polycondensation. However, these methods result in polydisperse particle sizes, and the polymerization techniques involved are complex. In this context, it is necessary to explore a new method to prepare monodisperse microcapsules with uniform size and uniform polymer shell thickness. A promising approach is droplet-based microfluidics, which enables precise control of the liquid phase, allowing the generation of well-defined emulsion droplets with specific shape, structure, composition, and uniform size distribution. These droplets can then be used as templates for the preparation of microcapsules with controllable, uniform, and highly spherical size. Li et al. recently prepared microencapsulated phase change materials (MEPCMs) using n-heptane as the core material and hexanediol diacrylate 3 (HDDA) polymer as the shell material using glass capillary microfluidics. Their results showed that the resulting bifunctional microcapsules had a smooth surface, spherical shape, and uniform size distribution. In addition, they confirmed that the bifunctional microcapsules with HDDA shell layer had good thermal properties. Fu et al. prepared elastic silicone / n-hexadecyl bromide microcapsules using a microfluidic method with co-flow channels, representing a new type of microencapsulated phase change material. This technique produced dual oil / oil / water (O1 / O2 / W) droplets with a core-shell structure. The results showed that these microcapsules have significant energy storage capacity, with a melting enthalpy of 76.35 Jg-1 and a freezing enthalpy of 78.67 Jg-1. Thermogravimetric analysis (TGA) confirmed their impressive thermal stability, while optical microscopy revealed the elastic properties of the silicone shell, allowing it to accommodate expansion. However, such capillary-based microfluidic devices are expensive, laborious, and operator-dependent. Therefore, there is a need to develop a cheap, simple, recyclable, and portable microfluidic device to create double emulsion droplets.
[0003] Furthermore, incorporation of inorganic nanoparticles into polymer matrices can significantly enhance the mechanical, electrical, optical, magnetic, and barrier properties of the matrix polymer. The synergistic effects between nanofillers and carrier polymers have been exploited in various fields such as food packaging, catalysis, controlled drug delivery, and photovoltaics. Titanium dioxide (TiO2) is a chemically stable, cost-effective, nontoxic material with excellent photocatalytic activity, antimicrobial properties, optical properties, and high UV protection. TiO2 is able to decompose organic compounds in water under UV irradiation and produce hydrogen as a byproduct. However, separation of TiO2 nanoparticles from aqueous dispersions after photocatalysis is a challenge. Attaching TiO2 to solid particles offers a practical solution that allows for direct particle separation and reduces concerns about ecotoxicological risks of residual TiO2 in water. To reduce separation costs, larger support particles are preferred, but their size can hinder the access of photons and create internal mass transfer limitations for TiO2. The optimal placement is to embed TiO2 in a thin support layer or polymer matrix. This arrangement improves encapsulation efficiency by exploiting the ability of TiO2 to change porosity and shrink the polymer network. In this way, the diffusion of TiO2 nanoparticles is improved, promoting surface interactions while reducing separation costs. Nuumani et al. improved the encapsulation efficiency of TiO2 in polymer microspheres by immobilizing TiO2 nanoparticles in microspheres made from a glass capillary microfluidic device. These microspheres showed effective methylene blue degradation under UV light, with a dye degradation rate of 80% within 9 hours with only 0.5wt% TiO2 embedded in a poly (HDDA) matrix. Although the microspheres can be easily recovered from water and maintain reliable photocatalytic performance over multiple cycles, the study mainly explored the photocatalytic properties of the multifunctional capsules, emphasizing their limitations in heat storage and regulation capabilities. Summary of the invention
[0004] In view of the above-mentioned deficiencies of the prior art, the present application provides a phase-change dual-functional microcapsule prepared by needle-based microfluidics that is very suitable for various applications in biomedicine, urban residential and industrial environments, thereby utilizing its thermal energy storage and photocatalytic capabilities in building materials.
[0005] In order to solve the above technical problems, the technical solution adopted in this application is: a phase-change bifunctional microcapsule prepared based on needle-based microfluidics in a building material, the raw materials of which include bifunctional microcapsules and gypsum, and the addition amount of the bifunctional microcapsules in the gypsum is 1-5wt%.
[0006] Furthermore, the amount of the dual-function microcapsules added to the gypsum is 2-4 wt%.
[0007] Furthermore, the amount of the dual-function microcapsules added to the gypsum is 2.5-3.5 wt%.
[0008] Furthermore, the specific preparation process of the dual-functional microcapsules includes: n-hexadecane is used as a paraffin material and as an internal phase fluid, HDDA (1,6-hexanediol diacrylate) and 1-3wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-3wt% of TiO2 are used as an intermediate phase fluid, and HMPP is also included as a photoinitiator, which can initiate HDDA polymerization under ultraviolet radiation; using a polyvinyl alcohol containing 6-9wt% and 1-3% poly (ethylene glycol) Deionized water of block-poly(propylene glycol)-block-poly(vinyl alcohol) was used as the external phase fluid; single emulsion droplets were formed in the coaxial section, and then the droplets further developed into double emulsion droplets after flowing into the co-flow section; the geometry and size of the O / O / W double emulsion droplets were adjusted by controlling the flow rate of the internal phase; the prepared droplets completed photopolymerization reaction in a capillary glass tube under ultraviolet radiation (365nm) to form bifunctional microcapsules with a core-shell structure, and after filtering, washing and drying, the bifunctional microcapsules were finally obtained.
[0009] Furthermore, the added amount of the photoinitiator is 2-3 wt %.
[0010] Furthermore, the flow rate of the external phase material is 305-450 μL min -1 The flow rate of the intermediate phase material is 20-30 μL min -1 The flow rate of the inner phase material is 15-25 μL min -1 .
[0011] Furthermore, the present application also provides a specific preparation method for the above-mentioned phase change dual-function microcapsules prepared based on needle-based microfluidics in building materials, the process comprising: (1) first pouring part of the molten gypsum into the mold, then adding 1-5wt% of microcapsules, cooling and solidifying at room temperature so that the microcapsules are evenly distributed inside the gypsum; (2) in order to completely cover the microcapsules and solidify the microcapsules inside the gypsum, pouring part of the molten gypsum into the mold, cooling and solidifying again at ambient temperature, and then demolding, finally obtaining a gypsum model house containing dual-function microcapsules.
[0012] Furthermore, the preparation method further comprises: heating the gypsum material containing the dual-functional microcapsules to melt the microcapsules, and heating the gypsum material at an ambient temperature of 8°C and 230W / m 2 A temperature test experiment was carried out on the plaster model house under simulated solar radiation. During this process, the microcapsules melted and absorbed heat. Then the house was allowed to cool naturally in a constant environment of 8°C to solidify the microcapsules. The microcapsules released heat during the solidification process.
[0013] The present application also provides an application of the above-mentioned phase change dual-function microcapsules prepared based on needle-based microfluidics in building materials, which are specifically used for thermal regulation of building materials. They have temperature regulation capabilities, namely thermal regulation functions and energy. In radiation heating and natural cooling experiments, buildings embedded with microcapsules show stronger thermal inertia than buildings without microcapsules, which means that the indoor and outdoor temperature changes of buildings with microcapsules are smoother, especially in the melting or solidification stage of the microcapsules; especially in the phase change process of the microcapsules, significant latent heat transfer occurs, resulting in smoother temperature changes of the buildings with microcapsules during heating and cooling.
[0014] Advantages and benefits of this application:
[0015] 1. This application is the first to use bifunctional microcapsules prepared based on needle-based microfluidic technology in building materials. The bifunctional microcapsules prepared by this specific process have temperature regulation capabilities, namely, heat regulation functions and energy. In radiation heating and natural cooling experiments, buildings embedded with microcapsules show stronger thermal inertia than buildings without microcapsules, which means that the indoor and outdoor temperature changes of buildings with microcapsules are smoother, especially in the melting or solidification stage of the microcapsules; especially in the phase change process of the microcapsules, significant latent heat transfer occurs, resulting in smoother temperature changes of buildings with microcapsules during heating and cooling; for example, after 10 minutes of heating, the indoor temperatures of the buildings with and without microcapsules are 19.15°C and 24.05°C, respectively, that is, the temperature of the house without microcapsules is 25.6% higher than that of the house with microcapsules. In addition, it can be seen from the temperature distribution curve that the temperature distribution of the outer wall of the microcapsule house is more uniform. This is because the thermal conductivity of TiO2 in the microcapsule (10W / (mK)) is higher than that of HDDA and hexadecane (<1(W / (mK)), so the microcapsule house has a higher thermal conductivity and enhances heat transfer. In addition, since the specific heat capacity of gypsum (about 1000J / (kg·K)) is lower than that of hexadecane (>2000J / (kg·K)), the thermal regulation performance of the building without microcapsules is not as good as that of the building with microcapsules. Therefore, even before reaching 20°C, in the absence of phase change, the temperature rise rate of the building without microcapsules is faster than that of the building with microcapsules; in summary, the house with microcapsules has better thermal regulation performance than the house without microcapsules.
[0016] 2. The thermal stability of the dual-function capsules is crucial for their practical application and depends largely on the quality of the capsule shell. To this end, thermogravimetric analysis (TG) and thermal cycling durability tests were performed on the dual-function capsules; the thermogravimetric curves of three substances, pure hexadecane, pure HDDA, and dual-function capsules with HDDA shells, were analyzed, and the weight of all three substances decreased with increasing temperature. Pure hexadecane began to lose weight at around 68.4°C and continued this trend until it reached 236.2°C, at which point it completely evaporated. It is worth noting that the decomposition temperature of pure hexadecane is lower than its boiling point of 292°C, indicating that the substance evaporated before reaching its boiling point. In contrast, the dual-function capsules with HDDA shells showed a significantly slower weight loss rate compared to pure PCM. The thermal decomposition of these capsules was essentially completed at around 480°C. In addition, the 5% weight loss temperature, indicating thermal resistance, was about 124.3°C for the capsules with HDDA shells. These findings indicate that the HDDA polymer shell effectively protects the PCM from leakage or rapid evaporation. Essentially, TG analysis and thermal cycle durability tests showed that the dual-function capsules with HDDA shell had higher thermal stability compared to pure n-hexadecane, with the HDDA polymer acting as a protective barrier against leakage or rapid evaporation.
[0017] 3. Size-controllable n-hexadecane / (HDDA) / TiO2 core-shell microspheres were prepared using a needle-based microfluidic device. During the droplet generation process, the shell thickness was controlled by adjusting the fluid flow rate to achieve customization of the microcapsule carrying capacity and mechanical strength; TiO2 nanoparticles were uniformly incorporated into the polymer shell; the shell can act as a photocatalyst in water, effectively degrading methylene blue under ultraviolet light, and can be easily recycled without reducing the catalytic efficiency; at the same time, the core area can act as a phase change material to achieve thermal regulation and energy storage; in addition, compared with houses without microcapsules, the indoor and outdoor wall temperature changes of houses with dual-function microcapsules are more moderate, especially during the melting or solidification stages; in addition, the microcapsule house responds faster to changes in ambient temperature and the temperature distribution of the exterior wall is more uniform; therefore, this specific microcapsule of the present application provides new options for various applications in the biomedical field, urban residential buildings in polluted areas, and industrial environments as a means of thermal energy storage, thermal regulation, and pollution control.
[0018] 4. The microcapsules used for materials in the present application have good mechanical properties. When the inner phase and the middle phase are 20μl / min and 25μl / min respectively, the wall thickness of the microcapsules is relatively thin, the final spacing is about 75μl, and the corresponding stress value is relatively large, which is 50.02N. On the contrary, when the flow rates of the inner phase and the middle phase change to 15 / 30μl / min, the wall thickness of the microcapsules increases, and the corresponding final spacing also increases slightly (100μl / min); while the stress value is slightly smaller at 49n. Based on the above analysis, the mechanical strength of the microcapsules can be improved with the increase of the shell thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of catalyst-loaded PCM microcapsules prepared by needle-based microfluidic device and thermal control system.
[0020] Figure 2 This is a schematic structural diagram of a cross-sectional view of the needle-based microfluidic device of the present application.
[0021] As shown in the attached figure: a. main channel, a1. first main channel, a2. second main channel, 1. first branch channel, 2. second branch channel. 3. third channel.
[0022] Figure 3 In different Q i / Q m (a) Optical microscope image of O / O / W droplets produced under the microscope and (b) inner diameter, outer diameter, and shell thickness distribution of O / O / W droplets. The scale bar on (a) represents 500 μm.
[0023] Figure 4 Particle size distribution of microcapsules.
[0024] Figure 5 Thermal regulation experiment setup of Example 1 of the present application (Room A: pure gypsum; Room B: 3 wt % phase change material capsules embedded in gypsum).
[0025] Figure 6 Temperature regulating performance of the phase change material capsule of Example 1 of the present application: (a) temperature changes of two prototype rooms during the heating process; (b) infrared thermal image capturing the heating process; (c) temperature fluctuations during the cooling stage; (d) infrared thermal image illustrating the cooling stage.
[0026] Figure 7 DSC curves of pure n-hexadecane and bifunctional microcapsules with a flow rate ratio of inner phase to middle phase of 4 / 5.
[0027] Figure 8 (a) SEM image of solid microcapsules; (b) broken core-shell microcapsules.
[0028] Fig. 9 (a) Absorbance test at different flow rates (b) Absorbance test at different illumination times.
[0029] Fig.10 Absorbance test at different microcapsule contents.
[0030] Fig.11 TG curves of n-hexadecane, HDDA and bifunctional microcapsules.
[0031] Fig.12 Axial force and clearance at different flow rates. DETAILED DESCRIPTION
[0032] The following will combine the embodiments and drawings to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only preferred embodiments, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention;
[0033] It should also be noted that when a component is referred to as being "fixed to" another component, it may be directly on the other component or there may also be another intermediate component, fixed through the intermediate component. When a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be another intermediate component at the same time. When a component is considered to be "set on" another component, it may be directly set on the other component or there may be another intermediate component at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0034] Example 1
[0035] First, partially melted gypsum is poured into a mold, and then 3wt% of dual-function microcapsules are added, and cooled and solidified in a natural environment;
[0036] Then, partially melted plaster is poured into the mold, covered with the dual-function microcapsules, and cooled and solidified in a natural environment to obtain the attached Figure 5-6 The gypsum house structure shown; since the density of the microcapsules is lower than that of the molten gypsum, during the solidification process, the microcapsules will be suspended on the surface of the molten gypsum and then solidified on the surface of the gypsum. Therefore, in order to avoid the above situation, part of the gypsum is laid first, then the dual-function microcapsules are laid, and finally part of the molten gypsum is laid to form a sandwich structure to encapsulate the dual-function microcapsules inside the gypsum.
[0037] Combined with Figure 1-2 The specific preparation steps of the dual-function microcapsules used in the embodiment of the present application are as follows:
[0038] (1) First, configure the microfluidic device (see Appendix Figure 1-2) in which n-hexadecane is used as paraffin material and is used as the inner phase fluid (inner phase); HDDA, 2wt% TiO2 and 2.0wt% 2-hydroxy-2-methyl-1-phenyl-1-propanone are used as the middle phase fluid, and a photoinitiator is added, HMPP is a photoinitiator that can initiate HDDA polymerization under ultraviolet radiation, and its addition amount is 1.5wt% (HDDA is used as a solvent); deionized water containing 8.0wt% polyvinyl alcohol and 2% poly(ethylene glycol) block-poly(propylene glycol)-block-polyvinyl alcohol is used as the outer phase fluid (outer phase);
[0039] (2) Then introduce the above-configured inner phase material, outer phase material and middle phase material into Figure 1-2 In the microfluidic device shown, the inner phase material is introduced into the first main channel a1 of the main channel a of the microfluidic device, the middle phase material is introduced from the first branch channel 1 into the second main channel a2 of the main channel a, and the outer phase material of the microfluidic device is introduced into the two second branch channels 2 of the microfluidic device; and the first branch channel 1 is closer to the introduction end of the inner phase material; wherein Q o (external phase) = 400 μL min-1, wherein Q m (middle phase) + Qi (internal phase) = 45 μL min-1, wherein Q o, Q m and Qi are the flow rates of the outer phase, middle phase and inner phase in the microfluidic device respectively; the three-phase materials are simultaneously introduced into the corresponding introduction ports of the microfluidic device for reaction;
[0040] (3) As the phase materials flow in the microfluidic device, single emulsion droplets are formed in the coaxial section (the tail end of the first main channel and the second main channel), and then the droplets further develop into double emulsion droplets after flowing into the co-flow section (through the shear position section of the second branch channel); for details, please refer to the attached Figure 1 The schematic diagram of the formation principle shown on the upper left;
[0041] (4) The prepared droplets are subjected to photopolymerization reaction in a capillary glass tube (third channel 3) under ultraviolet radiation (365 nm) to form dual-functional microcapsules with a core-shell structure.
[0042] The microfluidic device described above specifically adopts a needle-based microfluidic device, which includes a transparent polyethylene tube, a transparent polypropylene, a cross-connected male Luer connector, a stainless steel distribution needle, a transparent silicone tube and a transparent three-way tube. Figure 1-2As shown, the coaxial microfluidic device consists of a coaxial part and a co-flow part, which are composed of two distribution needles, two male Luer connectors, a transparent three-way tube and a cross-connecting tube. A 1 / 2-inch 19G distribution needle (ID = 0.84mm, OD = 1.08mm), a 1-inch 18G capillary glass tube (ID = 0.9mm, OD = 1.1mm) and a 1.6mm cross-connecting tube are used to form the coaxial part; then, a 2.0-inch 23G distribution needle (ID = 0.33mm, OD = 0.63mm) is inserted into the 19G needle through a T-connector (TL = 20mm, ID = 1.0mm, OD = 1.6mm) and a male Luer connector (TL = 14mm, ID = 1mm, OD = 1.6%) to assemble the co-flow part.
[0043] Characterization of bifunctional microcapsules: The O / O / W microdroplets were monitored by an optical microscope equipped with a high-speed camera. Scanning electron microscopy was used to observe the surface morphology of the bifunctional microcapsules. The average size and coefficient of variation of the droplets / bifunctional microcapsules were determined by measuring the size of the double emulsion droplets from the recorded pictures using ImageJ, where the coefficient of variation was a value calculated by the ratio of the average size of the bifunctional microcapsules to the standard deviation of the particle size. The phase transition properties of the bifunctional microcapsules were measured by differential scanning calorimetry. In this study, more than 3 DSC and SEM tests were performed under each fixed condition to reduce the experimental uncertainty.
[0044] When γ i-o >γ m-o +γ i-m When γ i-o , γ m-o and γ i-m The internal-external interfacial tension, the middle-external interfacial tension and the internal-middle interfacial tension are respectively. This application forms dual-functional microcapsules by only changing the internal flow rate, and all experiments are carried out under the following conditions: Q o =400 μL min -1 and Q m +Q i =45 μL min -1 , where Q o and Q m and Q i are the flow rates of the outer phase, middle phase and inner phase respectively. Figure 3 (a) shows the i / Q m The double emulsion droplets formed at the ratio of . Obviously, the obtained O / O / W droplets have a regular structure and uniform size. Figure 3 (b) shows the corresponding outer diameter (D o ), inner diameter (D i) and shell thickness (T s ). Obviously, by fixing the sum of the flow rates of the inner phase and the middle phase, and the flow rate of the outer phase, the outer diameter of the microcapsule remains unchanged, and as Q i / Q m As the value of increases, the inner diameter increases, while the shell thickness decreases. This is because for a particular microfluidic device, D o Depends only on Q o The flow rate and Q i +Q m For a fixed D o The encapsulated droplet, T s and D i Only by Q i / Q m The value of is determined.
[0045] Particle size distribution: Size monodispersity is an important indicator for evaluating dual-functional microcapsules prepared by combining UV curing and microfluidics. Figure 4 As shown in Q o =400 μL min -1 , Q m =25 μL min -1 and Q i =20 μL min -1 The particle size distribution produced under the conditions of 100 μm / min showed that the dual-function microcapsules had a uniform size distribution. The size variation was about 30 μm, and the size variation coefficient was about 7.5%. By repeating the experiment, we confirmed that the size distribution of different Q i / Q m The maximum value of the size variation coefficient under the conditions of RT-PCR was less than 8%, which demonstrated that the combination of radiation curing and needle-based microfluidics method can obtain dual-functional microcapsules with good monodispersity and high uniformity.
[0046] Thermal regulation of dual-functional microcapsules: In order to characterize the temperature regulation ability of dual-functional microcapsules, gypsum boards embedded with dual-functional microcapsules were made to conduct temperature regulation performance experiments (see Figure 5-6 The preparation process of the house is roughly as follows: pour part of the molten gypsum into the mold, add 3wt% microcapsules, condense and solidify in a natural environment, pour part of the molten gypsum into the mold, cover the microcapsules, condense and solidify in a natural environment, and finally complete the process. Two prototype houses were built according to whether microcapsules were added: House A with pure gypsum walls and House B with microcapsules embedded in the upper and lower walls. Figure 5 As shown, the houses are heated to melt the microcapsules and heated at 230W / m 2 Temperature regulation experiment was carried out under simulated solar radiation (see Figure 6 (a, b)), and then naturally cooled in a constant 8°C environment to solidify the microcapsules (see Figure 6(C, d)). In the experiment, an infrared thermal imager (HIKMICROP20Max) was used to capture thermal images of the house, and the temperature inside the house was characterized by a thermocouple placed in the center. In general, in both the radiative heating and natural cooling experiments, house B embedded with microcapsules showed stronger thermal inertia than house A without microcapsules. This means that the indoor and outdoor temperature changes of house A are more gradual, especially during the melting stage of the microcapsules (e.g. Figure 6 (a) and (b)) or solidification stage (as shown in Figure 6 (c) and (d)). In particular, during the phase change of the microcapsules, significant latent heat transfer occurs, resulting in a smoother temperature change in chamber B during heating and cooling. Figure 6 As shown in a, after 10 minutes of heating, the indoor temperatures of House B and House A were 19.15℃ and 24.05℃, respectively, that is, the temperature of House B without adding microcapsules was 25.6% higher. In addition, it can be seen from the temperature distribution curve that the temperature distribution of the outer wall of the microcapsule house is more uniform. This is because the thermal conductivity of TiO2 in the microcapsule (10W / (mK)) is higher than that of HDDA and hexadecane (<1(W / (mK)), so the microcapsule house has a higher thermal conductivity and enhances heat transfer. In addition, since the specific heat capacity of gypsum (about 1000J / (kg·K)) is lower than that of hexadecane (>2000J / (kg·K)), the thermal regulation performance of House A is not as good as that of House B. Therefore, even before reaching 20℃, in the absence of phase change, the temperature of House A rises faster than that of House B. In summary, the house with microcapsules has better thermal regulation performance than the house without microcapsules.
[0047] Thermal properties: The thermal storage properties of the bifunctional microcapsules can be evaluated by DSC analysis. Figure 7 The melting and freezing DSC curves of bifunctional microcapsules prepared for pure hexadecane when the flow rate ratio of the inner and middle phases is 4 / 5. Since only PCM undergoes phase change in the temperature range of -40.0℃-40.0℃, it can be seen that the bifunctional microcapsules with HDDA shell absorb and release less heat energy than pure hexadecane. Table 1 gives the freezing enthalpy and melting enthalpy data of pure core PCM, which are 272.90 and 268.93 kJ / kg, respectively. When the ratio Qi / Qm is 2 / 7, 3 / 6, 4 / 5 and 5 / 4, the fusion heat (ΔHf) of the bifunctional capsules is measured to be 92.49, 113.78, 138.41 and 153.29 kJ / kg, respectively, and the corresponding fusion heat (ΔHm) is 102.42, 126.26, 147.93 and 164.25 kJ / kg, respectively. The energy storage efficiency (E) and encapsulation efficiency (W) of the dual-function capsule can be calculated by the following formula:
[0048]
[0049] Table 1 Thermal properties of the prepared dual-functional microcapsules
[0050]
[0051]
[0052] The above results indicate that the dual-functional microcapsules prepared by needle-based microfluidics and UV radiation curing can be well used in latent heat storage systems.
[0053] Microstructure of bifunctional microcapsules: The concentric configuration of double emulsion droplets was permanently stabilized by photopolymerization using UV light curing technology. This method facilitates the preparation of bifunctional capsules with polymer shells. The integrity and flexibility of the shell play a key role in the various applications of bifunctional capsules, and these properties depend on the chemical composition of the shell material itself. In order to obtain bifunctional capsules with smooth surfaces and optimal compactness, it is necessary to expose them to UV radiation for an appropriate duration. Figure 8 The microstructure of the dual-function capsules directly formed by double emulsion droplets as templates is shown. Figure 8 As shown, the resulting bifunctional capsules exhibited a uniform spherical shape with a smooth surface while still maintaining the symmetrical core-shell structure of the double emulsion droplets. When comparing the double emulsion droplets with the final bifunctional capsules, it was noted that they had similar geometric dimensions. These findings highlight the efficacy of UV radiation curing in converting double emulsion droplets into bifunctional capsules through rapid polymerization without causing significant changes in their size and structure.
[0054] Photocatalytic activity of the dual-functional microcapsules: The photocatalytic activity of the TiO2-loaded microspheres was evaluated by degradation of methylene blue solution from aqueous solution under UV light. The maximum absorbance wavelength of methylene blue solution is 664 nm. Fig. 9 (a) shows that when 0.6 g of dual-function microcapsules were added to 1 mg / L methylene blue solution, the absorbance of the methylene blue solution increased with the increase of the flow rate ratio of the inner phase to the outer phase after half an hour of photocatalysis. Fig. 9 (b) It can be seen that under a certain flow rate ratio, the absorbance of the methylene blue solution gradually decreases with the increase of illumination time, and it can be completely degraded within two hours. Fig.10 The results show that the absorbance of the methylene blue solution without microcapsules without UV irradiation is basically the same as that with UV irradiation, which indicates that the pure methylene blue solution will not spontaneously degrade under UV irradiation. Fig.10It can also be seen that when 10 ml of methylene blue solution contained 0.6 g or 1 g of microcapsules, methylene blue could be completely degraded after 2.5 hours of UV irradiation, while a methylene blue solution containing only 0.2 g of microcapsules could only be degraded by about 50%. The resulting particles can be easily recycled and reused, an important feature for industrial applications. These results indicate that polymer particles embedded with TiO2 can be used as an effective recyclable photocatalyst. The ability to uniformly embed TiO2 nanoparticles within a polymer shell opens up new possibilities for the fabrication of bifunctional microparticles, in which the core and shell regions are associated with different functions. For example, the polymer shell can be used to achieve photocatalytic degradation of methylene blue under UV light, while the core region can be loaded with phase change materials and used for UV and visible light thermal energy storage.
[0055] Thermal stability of dual-function microcapsules: The thermal stability of dual-function capsules is crucial for their practical applications and largely depends on the quality of the capsule shell. To this end, thermogravimetric analysis (TG) and thermal cycling durability tests were performed on the dual-function capsules. Fig.11 Thermogravimetric curves of three substances, pure n-hexadecane, pure HDDA, and dual-function capsules with HDDA shells, are shown. All three substances lost weight as the temperature increased. Pure n-hexadecane began to lose weight at around 68.4 °C and continued this trend until it reached 236.2 °C, at which point it completely evaporated. It is noteworthy that the decomposition temperature of pure n-hexadecane was lower than its boiling point of 292 °C, indicating that the substance evaporated before reaching its boiling point. In contrast, dual-function capsules with HDDA shells exhibited a significantly slower rate of weight loss compared to pure PCM. The thermal decomposition of these capsules was essentially completed at around 480 °C. In addition, the 5% weight loss temperature, indicating thermal resistance, was approximately 124.3 °C for capsules with HDDA shells. These findings suggest that the HDDA polymer shell effectively protects the PCM from leakage or rapid evaporation. In essence, TG analysis and thermal cycling durability tests show that dual-function capsules with HDDA shells have higher thermal stability compared to pure n-hexadecane, with the HDDA polymer acting as a protective barrier against leakage or rapid evaporation.
[0056] Mechanical properties of dual-function microcapsules: The mechanical strength of the microcapsules was determined using a Haake RheoStress 6000 rotational rheometer with a parallel plate titanium alloy rotor P60 TiL at an experimental temperature of 25.0±0.1°C. The mechanical strength was determined by a compression test: a single microcapsule was laid flat on a parallel plate with an initial gap of 1 mm and compressed at a speed of 0.01 mm / s. The normal stress value during the compression process was also collected. Fig.12It can be seen that when the inner phase and the middle phase are 20μl / min and 25μl / min respectively, the wall thickness of the microcapsule is relatively thin, the final spacing is about 75μl, and the corresponding stress value is large, which is 50.02N. On the contrary, when the flow rate of the inner phase and the middle phase changes to 15 / 30μl / min, the wall thickness of the microcapsule increases, and the corresponding final spacing also increases slightly (100μl / min). The stress value is slightly smaller at 49n. Based on the above analysis, the mechanical strength of the microcapsule can be improved with the increase of the shell thickness.
[0057] Example 2
[0058] First, molten gypsum was poured into a mold, and then 3wt% of dual-function microcapsules were added and dehydrated;
[0059] Then, the molten plaster containing the dual-functional microcapsules is poured into the mold and dehydrated to obtain the attached Figure 1-2 The plaster house structure shown.
[0060] The dual-function microcapsules are prepared by the process described in Example 1.
[0061] It can be seen from the above examples that the present application uses a needle-based microfluidic device to prepare size-controllable n-hexadecane / (HDDA) / TiO2 core-shell microspheres. Through the droplet generation process, the shell thickness is controlled by adjusting the fluid flow rate to achieve the customization of the microcapsule carrying capacity and mechanical strength. The TiO2 nanoparticles are uniformly incorporated into the polymer shell, which provides an interesting opportunity for the production of multifunctional microcapsules with different functions in its core and shell regions. The shell can be used as a photocatalyst in water, effectively degrading methylene blue under ultraviolet light, and is easy to recycle without reducing the catalytic efficiency. At the same time, the core region can be used as a phase change material to achieve thermal regulation and energy storage. In addition, compared with houses without microcapsules, the indoor and outdoor wall temperature changes of houses with dual-function microcapsules are more moderate, especially in the melting or solidification stage. In addition, the microcapsule house responds faster to changes in ambient temperature and has a more uniform temperature distribution on the exterior wall. Therefore, the prepared microcapsules provide new options for various applications in the biomedical field, urban residential buildings in polluted areas, and industrial environments as a means of thermal energy storage, thermal regulation, and pollution control.
Claims
1. A building material of phase-change dual-function microcapsules prepared by needle-based microfluidics, characterized in that: The raw materials of the material include dual-function microcapsules and gypsum, and the addition amount of the dual-function microcapsules in the gypsum is 1-5wt%.
2. The phase-change dual-function microcapsule prepared by needle-based microfluidics in building materials according to claim 1 is characterized by: The addition amount of the dual-function microcapsules in the gypsum is 2-4wt%.
3. The building material of phase-change dual-function microcapsules prepared by needle-based microfluidics according to claim 2, characterized in that: The addition amount of the dual-function microcapsules in the gypsum is 2.5-3.5wt%.
4. The building material of phase-change dual-function microcapsules prepared by needle-based microfluidics according to claim 1, characterized in that: The specific preparation process of the bifunctional microcapsules includes: n-hexadecane is used as a paraffin material and as an internal phase fluid, HDDA and 1-3wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-3wt% of TiO2 are used as intermediate phase fluids, and HMPP is also included as a photoinitiator, wherein HDDA is a solvent; deionized water containing 6-9wt% of polyvinyl alcohol and 1-3% of poly(ethylene glycol)-block-poly(propylene glycol)-block-polyvinyl alcohol is used as an external phase fluid; single emulsion droplets are formed in a coaxial section, and then the droplets further develop into double emulsion droplets after flowing into a co-flow section; the geometric structure and size of the O / O / W double emulsion droplets are adjusted by controlling the flow rate of the internal phase; the prepared droplets complete a photopolymerization reaction in a capillary glass tube under ultraviolet radiation to form a bifunctional bifunctional microcapsule with a core-shell structure, and after filtering, washing and drying, the bifunctional microcapsule is finally obtained.
5. The building material of phase-change dual-function microcapsules prepared by needle-based microfluidics according to claim 1, characterized in that: The added amount of the photoinitiator is 2-3wt%.
6. The building material of phase-change dual-function microcapsules prepared by needle-based microfluidics according to claim 1, characterized in that: The flow rate of the external phase material is 305-450 μL min -1 The flow rate of the intermediate phase material is 20-30 μLmin -1 The flow rate of the inner phase material is 15-25 μL min -1 .
7. A method for preparing a building material of phase-change dual-function microcapsules prepared by needle-based microfluidics, characterized in that: The process includes: (1) First, a portion of the molten gypsum is poured into the mold, and then 1-5wt% of microcapsules are added, and the mold is cooled and solidified at room temperature so that the microcapsules are evenly distributed inside the gypsum. (2) In order to completely cover the microcapsules and solidify the microcapsules inside the gypsum, a portion of the molten gypsum is poured into the mold, and the mold is cooled and solidified again at ambient temperature, and then demolded to finally obtain a gypsum model house containing dual-functional microcapsules.
8. The method for preparing phase-change dual-function microcapsules in building materials based on needle-based microfluidics according to claim 7, characterized in that: The preparation method further comprises: heating the gypsum material containing the dual-functional microcapsules to melt the microcapsules, and heating the gypsum material at an ambient temperature of 8°C and 230W / m 2 A temperature test experiment was carried out on the plaster model house under simulated solar radiation. During this process, the microcapsules melted and absorbed heat. Then the house was allowed to cool naturally in a constant environment of 8°C to solidify the microcapsules. The microcapsules released heat during the solidification process.
9. An application of a building material of a phase-change dual-function microcapsule prepared by needle-based microfluidics according to any one of claims 1 to 7, characterized in that: The building material is used for thermal regulation of buildings.